220k views
0 votes
270 ÷ 9+(27+13)÷8 ⋅ 2–2 ⋅ (11–6)

User Tvirtualw
by
5.7k points

2 Answers

6 votes

Answer:30

Explanation:

There are three parts that need to calculate each and combine together.

270 ÷ 9+(27+13)÷8 ⋅ 22 ⋅ (11–6)

(1 ) (2) (3)

(1) 270 ÷ 9=30

(2) (27+13)÷8 ⋅ 2=40÷8 ⋅ 2=5 ⋅ 2=10

(3) 2 ⋅ (11–6)=2 ⋅ 5=10

(1)+(2)-(3)=30+10-10=30

User Jimy
by
5.3k points
4 votes

Answer:

270 ÷ 9+(27+13)÷8 ⋅ 2–2 ⋅ (11–6) = 30

Explanation:

The order of operation is written as BODMAS

BO - Bracket open

D - Division

M - Multiplication

A - Addition

S - Subtraction

We need to find 270 ÷ 9+(27+13)÷8 ⋅ 2–2 ⋅ (11–6)

Let us open the brackets first

270 ÷ 9+(27+13)÷8 ⋅ 2–2 ⋅ (11–6) = 270 ÷ 9+(40)÷8 ⋅ 2–2 ⋅ (5)

270 ÷ 9+(27+13)÷8 ⋅ 2–2 ⋅ (11–6) = 270 ÷ 9+40÷8 ⋅ 2–2 ⋅ 5

Now let us do the division part

270 ÷ 9+(27+13)÷8 ⋅ 2–2 ⋅ (11–6) = 30 + 5 . 2 -2 . 5

Now let us do the multiplication part

270 ÷ 9+(27+13)÷8 ⋅ 2–2 ⋅ (11–6) = 30 + 10 -10

Now let us do the addition part

270 ÷ 9+(27+13)÷8 ⋅ 2–2 ⋅ (11–6) = 40 -10

Now let us do the subtraction part

270 ÷ 9+(27+13)÷8 ⋅ 2–2 ⋅ (11–6) = 30

So 270 ÷ 9+(27+13)÷8 ⋅ 2–2 ⋅ (11–6) = 30

User Dimme
by
5.9k points